Does Upward Social Comparison on SNS Inspire Adolescent Materialism? Focusing on the Role of Self-Esteem and Mindfulness. Issue 1 (13th December 2022) - Hu, Yu-Ting; Liu, Qing-Qi; Ma, Zhen-Feng
Abstract: The present study tested the mediating role of self-esteem and the moderating role of mindfulness in the association between upward social comparison on social network sites (SNSs) and adolescent materialism. A sample of 880 Chinese adolescents completed measures of upward social comparison on SNSs, materialism, self-esteem, mindfulness, and demographic information. Results showed that self-esteem mediated the link between upward social comparison on SNSs and adolescent materialism. That is, upward social comparison on SNSs was positively associated with adolescent materialism through the decreased self-esteem. Moreover, mindfulness acted as an important moderator in the mediation model. Both the direct association between upward social comparison on SNSs and materialism and the indirect association via self-esteem were moderated by mindfulness. These two associations were both weaker for adolescents with higher mindfulness than for those with lower mindfulness. These findings would advance our understanding of how and when upward social comparison on SNSs is associated with adolescent materialism. Limitations and implications of the present study are discussed.